The Influence of The Rupiah Exchange Rate, Interest Rates and Inflation on Stock Prices : Case Study PT. Gudang Garam Tbk on The Idx for The 2015 – 2022 Period - Anggun Riyanti; Rita Tri Yusnita; Suci Putri Lestari (CV. Ulil Albab Corp, 2023)
The stock price is the main consideration for every investor or trader when they want to buy assets or shares in a company. This study aims to determine the effect simultaneously or partially of the rupiah exchange rate variable, interest rate variable and inflation variable. The population used in this study is the annual financial statements of PT. Gudang Garam Tbk in 2015-2022. The method used in this research is descriptive quantitative research. The sample selection uses a saturated sample. The sample used is the annual financial report of PT. Gudang Garam Tbk in 2015-2022. Source of data in this research is secondary data in the form of financial reports. The data analysis technique used is multiple linear regression with the help of SPSS 25. Based on the results of the study it was concluded that exchange rates, interest rates and inflation simultaneously have a significant effect on stock prices. The rupiah exchange rate partially has a significant effect on stock prices. Interest rates partially have a significant effect on stock prices. Inflation partially has a significant effect on stock prices